An Analysis of Student Ability in Understanding Noun Clause and Its Function: A Study of Student English Department in Academic Year 2018 at UNP - Ranti Melantari; Sitti Fatimah (Journal of English Language Teaching, 2020)
This study was students’ ability in understanding noun clause and its function: a study of students’ English department at UNP. The type of this research was descriptive quantitative research. According to the result of the research, the mean score of the students was 61.76. the students’ abilities in understanding noun clause and its function  that  had  2 students  or  8%  were  included  in the  highest  score  or  having  excellent  level.  8 students or 32%  students  were included  in  good  level.  Then,  10 students  or  40%  were  included  in  fair  level, 4 students  or  10%  students  were  included  in  poor  level  and  1  students  or  4% students  were  included  in  very  poor  level. It shows that the students’ ability  in understanding noun clause and its function of the students’ English language and literature department in academic year 2018 at UNP had fair level by mean score 61.76. They also do not master the concept of noun clause and how to use the noun clause itself in a sentence, and also they never practicing of the use of noun clause and its function well.